PELATIHAN PENYUSUNAN PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM, DESA CANGKUANG, KECAMATAN LELES, KABUPATEN GARUT - Andari, Diah; Fitriana , Rosa; Mulyati, Yati; Purnamasari , Dyah; Mariana, Citra (Jurnal Abdimas Bina Bangsa, 2025)
Community Service (PkM) will focus on the theme "Enhancing the Management of Cost Calculation for Goods Production among MSMEs in Cangkuang Village, Leles District, Garut Regency." The participants will include members of the Kominda Micro, Small and Medium Enterprises (UMKM) cooperative in Cangkuang Village, Leles District, Garut Regency. The primary objective of this initiative is to enhance the accuracy of production cost calculations for MSMEs in the area. Additionally, a specific aim of this PkM is to ensure that MSME operators comprehend the significance of accounting in their business operations and are equipped to conduct Management Counseling for the Preparation of Cost of Goods Production. This knowledge will enable MSME operators to effectively manage their finances and generate straightforward financial reports utilizing information technology, ultimately contributing to the growth of their businesses in the future.